Building strong early literacy through the reading reflection moment programme at SDN 1 Sarajaya - Tosuerdi; Nurfadiyah, Alfina (Prosiding Seminar Nasional Pengabdian Masyarakat, 2024)
Reading is a boring thing nowadays. Reading reflection moments are one of the efforts that the author chooses to solve problems in the field of education. The method used in this service article is the cooperative learning method. This service was carried out at SDN 1 Sarajaya, Lemahabang District, Cirebon Regency, with the aim of increasing students' motivation to read and study and increasing their self-confidence. This activity involved high class students, namely grades 4, 5 and 6. The results of the activity showed that students' interest and enthusiasm for reading had greatly increased.